Revisiting the celestine question in Inferno III: "Vidi e conobbi l´ombra di colui che fece per viltade il gran rifiuto" - Raffaele De Benedictis (Medievalia, 2016)
This study aims to respond to those who have identified Celestine V as the unquestionable referent of colui (him who) in Dante´s Inferno III, II.58-60.